Prevalence Of Low Back Pain Among Nurses And Its Impact On Their Nursing Job. - Adhikari, Susmita
ABSTRACT: identify the prevalent causes of low back pain and its impact among the nurses of Shahid Gangalal National Heart Centre. For the study, a total of 50 nurses from various departments i.e. ICU, CCU, Emergency, Cath Lab and Surgical ward were selected purposively. A semi structured self administered questionnaire was distributed to all study participants and collected after 2 days. Data was analyzed using the Statistical Package for the Social Sciences (SPSS) version 16 for windows. Descriptive statistics and cross tabulation were employed to summarize the data. According to study finding, 78% nurses of shahid Gangalal National Heart Centre were suffering from low back pain. It showed high prevalence of low back pain (78.3%) among the nurses of age equal to or less than 24 years than that of nurses more than 24 years (77.8%). Study also showed that 87.5% of married nurses were suffering from low back pain than that of unmarried nurses (69.2%). Similarly, 83.3% of nurses of ICU/CCU were suffering from low back pain than that of Cath lab/Emergency/ Surgical ward (70%). Some of the reasons for low back pain as perceived by the nurses were: Prolonged standing (82.1%), frequent bending and twisting (51.3%) and heavy physical workload (51.3%). According to study findings, most frequent activities which were always done by nurses were: medication (94%), receiving emergency patient (54%), bed making (52%), moving patient to different position (50%) and lifting and transferring patients (50%). Because of low back pain, 43.6% were unable to perform their job properly, 33.3% have become less productive and creative, increased work restriction among 28.2% and decreased in the quality of care to the patient among 25.6% nurses. This study suggests that three fourth of nurses from Shahid Gangalal National Heart Centre were suffering from low back pain which indicates high prevalence. Therefore, it was recommended to promote and conduct leisure time physical activities and preventive measures by the hospital in order to maintain a healthy and productive nursing staff.